The Okabayashi Radical Hysterectomy: Basic Principle and Step-by-Step Procedure - Konishi, Ikuo (The Surgery Journal, 2021)
Abdominal radical hysterectomy is the standard operation for stage IB–IIB cervical cancer in the world, which was established by Professor Hidekazu Okabayashi in 1921. In this article, the basic principle and step-by-step procedure of Okabayashi radical hysterectomy are presented, especially for young doctors to understand clearly the important points of this surgery and to realize its radicality and safety for better survival and quality of life of patients with cervical cancer.
Keywords: Okabayashi radical hysterectomy; basic principle; step-by-step procedure; cervical cancer